Hubungan Antara Hasil Belajar Akidah Akhlak Dengan Self Control Siswa MAN 2 Cilacap - Arum Septia Dyah Ayu Nurfajri; Sarno Hanipudin (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2023)
This research is motivated by the existence of akidah akhlak learning which has the aim of shaping the behavior of students from a negative to a positive one. The unstoppable development of the times has resulted in many impacts on students, one of which is the low self-control which will make students perform negative actions that are against the norm. This study aims to determine the relationship between the learning outcomes of akidah akhlak and self-control of students in class XI MAN 2 Cilacap in the 2021/2022 academic year. This study uses a quantitative approach with a population of 460 which will use 115 respondents with a simple random sampling technique. Collecting data using 4 methods, namely observation, interviews, documentation, and questionnaires. The research data that has been collected is then processed and analyzed. Of the two existing variables, namely variable X (the result of learning values ​​of akidah akhlak) which shows an average value of 82.49 and is included in the fairly good category. While the variable Y (self control) which shows an average value of 79.73 and is included in the good category. Hypothesis testing was analyzed using SPSS Version 25 with the Spearman rank. The results of hypothesis testing indicate that there is a positive relationship between the learning outcomes of aqidah morals and self-control of students in class XI MAN 2 Cilacap. This can be seen based on the results of the correlation test which shows a correlation coefficient of 0.259 with a significance (2-tailed) of 0.005 in 115 research samples with an rtable of 0.183. That is, between learning outcomes of morals and self-control , there is a significant relationship with the direction of the positive (+) or unidirectional relationship, with a low level of correlation.